First report on CRISPR/Cas9 based in vitro restriction of yellow genein the oriental fruit fly, Bactrocera dorsalis - DASH, SANGEETA; R, ASOKAN; NAIK D, JEMLA (The Indian Journal of Agricultural Sciences, 2025)
Bactrocera dorsalis (Hendel) is a serious pest that can cause significant financial losses. CRISPR/Cas9 is a reliable and effective approach for site-directed genome editing. The CRISPR/Cas9 system modifies DNA in a stable and heritable manner. Due to their complementary nature to the target gene, these artificially created single guide RNAs (sgRNAs) instruct the Cas9 endonuclease to produce double strand breaks in the gene sequence. This causes a functional disruption in target gene expression in the organism. The present study was carried out during 2020–2022 at ICAR-Indian Institute of Horticultural Research, Hessaraghatta, Bengaluru, aimed at the validation of genetic targets for genetic biological control of this notorious pest via CRISPR/Cas9 mediated genome editing at 560089. Gene yellow crucial for melanin pigmentation and body colouration in the insect was cloned followed by the synthesis of two (sg692 and sg915) off-target minimised guide RNA. The designed gRNAs were used for restriction assay to check the cleavage efficiency of sgRNAs. A successful in vitro cleavage of the gene was witnessed. Thus, our research proves the effectiveness of CRISPR/Cas9 mutagenesis as a suitable genetic control strategy for the management of pests of quarantine and economic significance.